2008
DOI: 10.1016/j.jada.2008.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Diet Quality Varies by Race/Ethnicity of Head Start Mothers

Abstract: Background-Despite the key role that women from limited income families play as family food providers and their high risk for diet-related chronic diseases, there is a paucity of data about their diet quality and how it might vary by race/ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 36 publications
4
26
0
Order By: Relevance
“…10,13,14 This study provides additional evidence that the authoritative feeding style, which has been associated with positive child eating behaviors, is uncommon among low-income mothers. 10,14 Therefore, education on parent feeding skills may benefit all low-income mothers.…”
Section: Discussionmentioning
confidence: 67%
“…10,13,14 This study provides additional evidence that the authoritative feeding style, which has been associated with positive child eating behaviors, is uncommon among low-income mothers. 10,14 Therefore, education on parent feeding skills may benefit all low-income mothers.…”
Section: Discussionmentioning
confidence: 67%
“…The latter system has been reported to overestimate whole grains intake, which concomitantly may result in underestimation of refined grains than when using the MyPyramid Equivalents Database (36) ; (ii) the present study included Mexican-American women only. In general, Hispanics have been reported to have higher dietary quality and consume more dietary fibre than individuals from other ethnic backgrounds (3,7,17) . Participants from both groups in the current study achieved the maximum score for total protein intake, as has been reported for the general US population (17,63) .…”
Section: Adequacy Components Of the Healthy Eating Index-2010mentioning
confidence: 99%
“…Poor dietary quality may be a major contributor to these disparities. Available surveillance data on dietary composition suggest that, as for other ethnic groups, the diet of Mexican-American adults is in need of improvement, as indicated by reports of high intakes of solid fats, cholesterol, added sugars and sugarsweetened beverages, and low intakes of vitamins D and E, Ca and K, whole grains, dairy products, dark greens and highly coloured vegetables (3)(4)(5)(6)(7) . Different ethnic subgroups have culture-bound patterns of food purchase, preparation and eating (8) , all of which can be affected by environmental resources (e.g.…”
mentioning
confidence: 99%
“…This may be due to stress from increased financial and time demands; food choices based on convenience as well as limited affordability and access to healthy foods may result in suboptimal diet quality, particularly among low-income women (Eikenberry & Smith, 2004; Reyes, Klotz, & Herring, 2013). NHB mothers in particular have been shown to have lower diet quality, higher risk of depression and greater amounts of weight retained during the postpartum period compared to non-Hispanic white (NHW) mothers (Everson, Maty, Lynch, & Kaplan, 2002; Gillman et al, 2001; Hoerr, Tsuei, Liu, Franklin, & Nicklas, 2008; Siega-Riz, Evenson, & Dole, 2004). …”
Section: Introductionmentioning
confidence: 99%